Educating for wisdom and compassion : creating conditions for timeless learning - Miller, John P., 1943- (Corwin Press, a Sage Publications Company, 2006)
Essential principles of timeless learning include attention, contemplation, connection, participation, and responsibility; helping students achieve a sense of purpose; and improving alertness and mental health